2020
DOI: 10.1158/1535-7163.mct-18-1320
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Responses of 2D and 3D Glioblastoma Cells: A Novel, 3D-specific Radioprotective Role of VEGF/Akt Signaling through Functional Activation of NHEJ

Abstract: Glioblastoma is resistant to conventional treatments and has dismal prognosis. Despite promising in vitro data, molecular targeted agents have failed to improve outcomes in patients, indicating that conventional two-dimensional (2D) in vitro models of GBM do not recapitulate the clinical scenario. Responses of primary glioblastoma stem-like cells (GSC) to radiation in combination with EGFR, VEGF, and Akt inhibition were investigated in conventional 2D cultures and a three-dimensional (3D) in vitro model of GBM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Finally, profiling of treated cancer cells within the scaffold led to the identification of candidate predictive biomarkers. Several evidences indicates that engineered 3D models can be useful approaches to study and identify drug resistance mechanisms to anticancer agents (76)(77)(78)(79)(80). Here we demonstrate that the molecular changes identified through our biomimetic model are i) predictive of in vivo molecular alterations on tumor xenografts and ii) demonstrate clinical predictive potential.…”
Section: Discussionsupporting
confidence: 58%
“…Finally, profiling of treated cancer cells within the scaffold led to the identification of candidate predictive biomarkers. Several evidences indicates that engineered 3D models can be useful approaches to study and identify drug resistance mechanisms to anticancer agents (76)(77)(78)(79)(80). Here we demonstrate that the molecular changes identified through our biomimetic model are i) predictive of in vivo molecular alterations on tumor xenografts and ii) demonstrate clinical predictive potential.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, systematic comparison of the VEGF-A secretion from conventional monolayer cell culture and 3D spheroid model has not been performed due to technical limitations. Cellular stresses in 3D spheroids have been observed to potentially trigger several pro survival pathways [2,20,25,37,44], where VEGF plays a major role [45,46]. Common challenges faced in the in vitro 3D culture models include tedious sample handling, maintaining uniformity and stability to avoid structural disintegration of spheroids.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using anti-cancer agents on spheroid systems have concluded that physical properties of spheroids are related to drug efficacy [50,51]. Furthermore, recent studies have also shown that cytokine secretion profiles are different between conventional monolayer cultures and 3D culture systems [46,52]. A tactful approach capable of direct quantitative characterization of VEGF protein is highly desired to investigate responses of multicellular spheroids under specific cellular stress conditions without delving into the intercellular variations which can be further compared to the clinical observations.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of a BRCA2-mutated clone that developed a resistance mutation and expressed a functionally wild-type protein, VEGFR3 inhibition was sufficient to restore chemosensitivity [110]. The inhibition of VEGF and VEGFR2 in organoid models prevented Akt-mediated DNA repair, thereby preventing HR and leading to aberrant NHEJ [111]. Anti-angiogenics are also hypothesized to induce or exacerbate intratumoral hypoxia, which itself is associated with impaired HR [112][113][114][115].…”
Section: Parpi and Anti-angiogenic Agentsmentioning
confidence: 99%